Nexus between Monetary Policy and Financial Inclusion in Nepal: An Autoregressive Distributed Lag Approach - Adhikari, Gyan Mani; Chalise, Mahananda; Chhetri, Santosh; Karki, Krishna Bahadur (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study examines the dynamic relationship between monetary policy instruments and financial inclusion in Nepal, analyzing how key monetary policy tools affect access to financial services. Design/Methodology/Approach: This study employs an Autoregressive Distributed Lag approach (ARDL) bounds testing approach on annual time series data from 1999 to 2024 to examine both short-run dynamics and long-run relationships between monetary policy instruments and financial inclusion in Nepal. The Financial Inclusion Index, constructed via Principal Component Analysis from deposit-to-GDP and creditto-GDP ratios, serves as the dependent variable, while key monetary policy tools and urban population share are included as explanatory variables. Findings: The ARDL bounds test confirms significant long-run relationships between monetary policy instruments and financial inclusion. Cash Reserve Ratio (CRR) exhibits a significant negative impact, while Standing Liquidity Facility (SLF) shows a marginally significant negative effect. Policy rate demonstrates no significant long-run impact. Urban population shows strong positive relationships. Implications: Policymakers should adopt coordinated approaches incorporating financial inclusion objectives into monetary frameworks, utilizing differential reserve requirements and targeted rural infrastructure investments. Originality/value: This research uniquely applies ARDL methodology to examine the monetary policy-financial inclusion nexus in Nepal, providing novel empirical evidence on differential impacts of specific monetary instruments and contributing to the limited South Asian financial inclusion literature. JEL Classification: E52, G21, G28, O16, R11